Chain Reduction via Substitution: Evidence from Mayan. Issue 1 (28th January 2021) - Mendes, Gesoel; Ranero, Rodrigo
We argue that deletion is not the only way that chain links created by A′-movement can be affected at PF. Chain links can also be substituted by a morpheme. This substitution delivers a linearizable output (in a manner parallel to deletion), creating overt "traces" on the surface. We demonstrate the virtues of our proposal through the empirical lens of adjunct extraction in two Mayan languages of the K'ichean branch: K'iche' and Kaqchikel. In these languages, extraction of low adjuncts triggers the appearance of a verbal enclitic wi . The distribution of the enclitic upon long distance extraction shows that it must be analyzed as a surface reflex of substitution of a chain link. Our proposal provides evidence that movement proceeds successive cyclically and has two additional theoretical consequences: (i) C 0 must be a phase head (contraden Dikken 2009 ;2017 ), (ii) v 0 cannot be a phase head (in line withKeine 2017 ).